A culpabilidade na caracterização da infração administrativa à ordem econômica - Vianna, Rodrigo França (2023)
The present work deals with the role of culpability in the characterization of administrative infractions to the economic order. The main objective of this study is to evaluate the doctrinal proposals for the interpretation of the expression "regardless of guilt" contained in the caput of art. 36 of Law nº 12.529/2011 and indicate the formulation best aligned with the Federal Constitution. It is a theoretical, legal-dogmatic analysis, under a hypothetical-deductive reasoning, developed on the methodological bases of logical-semantic constructivism, by Paulo de Barros Carvalho. The construction of the meaning of the norms analyzed was based on the tripartite formulation of Tércio Sampaio Ferraz Jr., “analytical, hermeneutic and pragmatic”, and the interpretation according to the Constitution was based on the theory of Constitutional Hermeneutics, by Lênio Streck. From an analytical perspective, the study extracts from the General Theory of Law the anatomy of the complete legal norm, focusing on the legal causality link between the antecedent and consequent norms. Under the hermeneutic and pragmatic perspectives, it defines the legal regime and interests protected. The study outlines the points of doctrinal consensus about sanctioning administrative law and chooses the panorama of analysis of the elements that structure an infraction from a comparison with the criminal and civil legal regimes. The study formulates a modulation proposal for legal principles for sanctioning administrative law and analyzes the structure of a legal offense, in the light of the finalist theory of criminal law, focusing on the principle of culpability. It then presents theories of causality and imputation of legal entities. When considering the foundations and purposes of the repressive legal regime, it establishes that the theory of normative (or objective) culpability and the theory of organizational failure to supervise are the most appropriate theories. The study applies these general formulations to the specific environment of Competition Law, analyzing the elements of violations of the economic order based on these theories. Then, the “theories of antitrust analysis”, typical of this antitrust law, are presented, and the compatibility of each one with the constructed precepts is analyzed. Finally, the study concludes by recommending the theory of normative culpability, as long as it is limited to the use of relative presumptions to verify the elements of the crime, which is not applicable in cases where the so-called per se rule is applied (that is, if the infraction is classified as formal)